Antibiotic concentrations in raw hospital wastewater surpass minimal selective and minimum inhibitory concentrations of resistant Acinetobacter baylyi strains. (10th November 2022) - Schuster, Dominik; Axtmann, Katharina; Holstein, Niklas; Felder, Carsten; Voigt, Alex; Färber, Harald; Ciorba, Patrick; Szekat, Christiane; Schallenberg, Anna; Böckmann, Matthias; Zarfl, Christiane; Neidhöfer, Claudio; et al.
Abstract: Antibiotics are essential for modern medicine, they are employed frequently in hospitals and, therefore, present in hospital wastewater. Even in concentrations, that are lower than the minimum inhibitory concentrations (MICs) of susceptible bacteria, antibiotics may exert an influence and select resistant bacteria, if they exceed the MSCs (minimal selective concentrations) of resistant strains. Here, we compare the MSCs of fluorescently labelled Acinetobacter baylyi strains harboring spontaneous resistance mutations or a resistance plasmid with antibiotic concentrations determined in hospital wastewater. Low MSCs in the μg/L range were measured for the quinolone ciprofloxacin (17 μg/L) and for the carbapenem meropenem (30 μg/L). A 24 h continuous analysis of hospital wastewater showed daily fluctuations of the concentrations of these antibiotics with distinctive peaks at 7–8 p.m. and 5–6 a.m. The meropenem concentrations were always above the MSC and MIC values of A. baylyi . In addition, the ciprofloxacin concentrations were in the range of the lowest MSC for about half the time. These results explain the abundance of strains with meropenem and ciprofloxacin resistance in hospital wastewater and drains.